Finally mine - Score, Lucy (Score, Lucy. Benevolence series., 2023)
"Aldo Moretta has always been the hero. The strongest, the fastest, the bravest. He fought for his country and built a thriving business in his hometown. With friends and family never more than a few blocks away, there was just one things he was missing. The right girl. She'd fallen for the wrong guy. The bad guy. But now that she's finally free, Also isn't going to miss his second chance. Not until his las deployment goes horribly wrong. He was prepared to give his life, but he wasn't ready for an injury that takes a piece of him. How can he be her hero now? Gloria Parker walked away from a relationship that almost cost her her life. But the shame clings to her like a shadow. She's wasted ten years on the wrong man. When the right one returns home scarred and broken, she sees a kindred spirit. But as Gloria rebuilds her life, brick by brick, she wonders if she's cut out for love. Real love. Will they find a way to heal together or will their wounds keep them from the happiness they both crave?"--